Hubungan Pemberian Kortikosteroid terhadap Kenaikan Berat Badan pada Anak Penderita Leukemia Limfoblastik Akut Fase Induksi di RSUP Haji Adam Malik Medan - Almira, Isni Dhiyah; Nafianti, Selvi (Talenta Publisher, 2021)
Background: Glucocorticoid corticosteroids have vasoconstrictive, anti-proliferation, anti-inflammatory, and immunosuppressant effects through interactions with glucocorticoid receptors which have also been found in one type of leukemia, acute lymphoblastic leukemia (ALL). The most common side effect long-term use of high dose corticosteroids is increase in body weight resulting in obesity. It is one of the main problems in ALL patients, because it leads to persistent leukemia, increase of the risk of recurrence, and poor event-free survival. This has been associated with the use of glucocorticoids namely dexamethasone and prednisone in the induction phase chemotherapy process. Objectives: This study was intended to determine the association of corticosteroid administration to weight gain in children with ALL induction phase. Methods: The study was analytic-cross sectional. A total of 62 medical records of pediatric patients with ALL in Haji Adam Malik General Hospital Medan in 2015-2018. The data obtained were processed using the Wilcoxon statistical test, the Mann-Whitney test, and the Spearman-Correlation Rank test. Results: Wilcoxon test showed the effect of corticosteroid administration on body weight in the sample (p = 0.001). The Mann-Whitney test showed a difference in the influence of the use of prednisone and dexamethasone on sample body weight (p = 0.001), but it was not found regarding the nutritional status of the sample (p = 0.149). The Spearman-correlation test showed that there was no association of weight gain with the total corticosteroid dose given (p = 0.251). Conclusion: There is an association of corticosteroid administration to body weight in children with ALL induction phase. There are differences in the influence of the use of prednisone and dexamethasone on body weight, while there is no such difference on nutritional status in children with ALL induction phase. There is no association of weight gain based on the total corticosteroid dose given during the induction phase in children with ALL. Keywords: acute lymphoblastic leukemia, corticosteroid, induction phase chemotherapy, weight gain Â Latar Belakang: Kortikosteroid golongan glukokortikoid memiliki efek vasokontriksi, anti-proliferasi, anti-inflamasi, dan imunosupresan melalui interaksinya dengan glucocorticoid receptor yang juga telah ditemukan pada salah satu jenis leukemia yaitu leukemia limfoblastik akut (LLA). Efek sampingÂ paling sering dari penggunaan kortikosteroid jangka panjang dengan dosis tinggi adalah peningkatan berat badan berlebih yang berakibat pada obesitas. Hal ini menjadi salah satu masalah utama pada pasien LLA, karena dapat menyebabkan leukemia persisten, meningkatkan risiko kekambuhan, dan event-free survival yang buruk. Hal tersebut telah dikaitkan dengan penggunaan glukokortikoid deksametason dan prednisone dalam proses kemoterapi LLA fase induksi. Tujuan: Penelitian ini dimaksudkan untuk mengetahui hubungan pemberian kortikosteroid terhadap kenaikan berat badan pada anak penderita leukemia limfoblastik akut fase induksi. Metode: Penelitian yang dilakukan bersifat analitik-cross sectional. Dikumpulkan sebanyak 62 rekam medis pasien anak penderita LLA di RSUP Haji Adam Malik Medan tahun 2015-2018. Data yang diperoleh diolah menggunakan uji statistik Wilcoxon, uji Mann-Whitney, dan uji Rank Spearman-Correlation. Hasil: Uji Wilcoxon menunjukkan adanya pengaruh pemberian kortikosteroid terhadap berat badan pada sampel (p = 0,001). Uji Mann-Whitney menunjukkan adanya perbedaan pengaruh penggunaan prednison dan deksametason terhadap berat badan sampel (p = 0,001), tetapi tidak terhadap status gizi sampel (p = 0,149). Uji Rank Spearman-Correlation menunjukkan tidak terdapat hubungan kenaikan berat badan terhadap total dosis kortikosteroid yang diberikan (p = 0,251). Kesimpulan: Terdapat hubungan pemberian kortikosteroid terhadap berat badan anak penderita LLA fase induksi. Terdapat perbedaan pengaruh penggunaan prednison dan deksametason terhadap berat badan anak penderita LLA fase induksi, tetapi tidak terhadap status gizi. Tidak terdapat hubungan kenaikan berat badan berdasarkan total dosis kortikosteroid yang diberikan selama fase induksi pada anak penderita LLA. Kata kunci: kemoterapi fase induksi, kenaikan berat badan, kortikosteroid, leukemia limfoblastik akut